PHOSPHORUS AND ZINC NUTRITION IN MAIZE (ZEA MAYS L.) UNDER DROUGHT STRESS - Tahseen Afzal; Abdul Wakeel; Tanvir Shahzad; Sabir Hussain; Muhammad Sanaullah (Journal of Animal and Plant Sciences, 2023)
Drought stress causes negative effects on soil nutrients dynamics as well as their mutual interactions. Negative interaction between phosphorus (P) and zinc (Zn) vis-à-vis plant uptake exists under adequate moisture availability but this phenomenon is still unclear under drought condition. A pot study was conducted to investigate the effect of this interaction on maize plants (var. FH-1046) at three moisture levels, viz., optimum (80% of water holding capacity-WHC), moderate drought (50% of WHC) and severe drought (30% of WHC). The P and Zn were added alone (only-P and only-Zn) or in combination (P + Zn) at the rate of 57 and 6 mg kg−1 soil at three moisture levels with complete randomization. Soil moisture levels were introduced after two week of plant growth and maintained after every three days by weighing. After 60 days of plant growth, plants were harvested and analyzed for their growth and nutrient contents, viz., P, Zn, nitrogen (N), and potassium (K). The findings showed that combined P and Zn caused a significant reduction in P and Zn contents at the root and shoot levels at higher moisture (80% and 50% of WHC) relative to alone P and Zn additions, but the extent of this reduction reduced with increasing drought intensity, showing the negative effect of drought on plant nutrient uptake. The effect of combined nutrients addition was positive on plant growth and the absence of P (only Zn addition) reduced plant height by 14 and 28% at 80% and 30% of WHC. Shoot and root dry weights increased significantly by 41 and 43% with combined P and Zn. The plant growth also declined with increasing drought level. Under severe drought, P and Zn negative interaction diminished considerably but there was an overall negative effect on plant growth and nutrient contents at 30% of WHC. The findings suggest that increasing drought intensity can reduce the negative effect of P and Zn on each other’s uptake and accumulation in plants but with concurrent reductions in absolute nutrient contents and plant growth.
Keywords: Phosphorus; Zinc; Drought; Maize; Water holding capacity